Immune Status of the Oral Cavity in Orthopedic Treatment - Abduvakilov Jaxongir Ubaydullayevich; Irgashev Shoxrux Xasanovich (Genius Journals, 2023)
The tasks of orthopedic dental treatment include not only the replacement of defects in the dentition or alveolar processes with prostheses, but also the prevention of their further destruction or recurrence of the disease. The prosthesis, therefore, is considered as a therapeutic agent, the reasonable use of which allows the implementation of therapeutic and preventive measures
Keywords: orthopedic; dental treatment